New GTC spectroscopic data and a statistical study to better constrain the redshift of the BL Lac RGB J2243 + 203 - Rosa González, D (2019)
We present new spectroscopic data of the BL Lac RGB 2243 + 203, and its surroundings, obtained with the OSIRIS Multi Object Spectrograph (MOS) mounted in the Gran Telescopio Canarias (GTC). The spectra of neither the BL Lac nor its host galaxy show any spectral feature, thus hindering direct determination of its redshift. The spectroscopic redshift distribution of objects in the MOS field of view shows four galaxies with redshift between 0.5258 and 0.5288. We make use of a statistical analysis to test the possibility that the targeted BL Lac may be a member of that group. By using the spectroscopic redshifts obtained with our GTC observations, we found that this probability is between 86 and 93 per cent.